Co-development of an acceptance and commitment therapy-based intervention to increase intrinsic motivation of adolescents to change weight: The AIM2Change study - Jennifer S. Cox; Aidan J. Searle; Idoia Iturbe; Gail A. Thornton; Ingram Wright; Claire Semple; Ken Clare; Julian P. Hamilton-Shield; Elanor C. Hinton (PLoS ONE, 2025)
Childhood obesity levels continue to rise, with significant impact on individuals and the NHS. The ‘Complications of Excess Weight’ (CEW) clinics provide support to young people with complications of their weight. Our objective was to co-develop, with young people, a new intervention; AIM2Change, to enable young people to develop their intrinsic motivation to manage weight, using Acceptance and Commitment Therapy (ACT), with a person-centred approach. Young people from the Care of Childhood Obesity (CoCO) clinic in Bristol, UK, were recruited to co-develop this intervention. The study was registered on ISRCTN (ISRCTN16607863). The seven-session, ACT-based intervention was delivered one-to-one, securely online. Qualitative interviews were conducted after each intervention session was delivered. Qualitative data were coded and reviewed regularly to make iterative changes to individual sessions and the overall programme. Fourteen co-developers were recruited, of whom nine completed the co-development process (female = 4; median age (IQR)=15(1.5); 4 with a parent; Indices of Multiple Deprivation (IMD) median = 3.5, range = 1–10). Iterative changes made during co-development included introducing an earlier focus on eating behaviour and body image, with more practical activities to increase engagement. Thematic analysis of co-developer feedback identified four themes: theoretical understanding; delivery and receipt of therapy; view of strategies and engagement; real world benefits of co-development process. Framework analysis was conducted to map data pertaining to these themes into matrices according to each participant and session. Insights from the co-development process have shaped AIM2Change to optimise the intervention’s value, relevance and acceptability. Findings suggest that AIM2Change meets an unmet need in delivery of current childhood weight management services.